Perawatan Pada Mesin Milling Menggunakan Metode Breakdown Pada Saat Table Milling Berhenti di PT. Oana Engineering Indonesia - Gamas Rizqilah; Kardiman Kardiman; Ratna Dewi Anjani (Peneliti.net, 2022)
Machine maintenance is early access or pre-planned maintenance of the problems that occur in each machine unit and has become an important part of today’s industry to avoid breakdowns because it can save costly errors, keep production continuing with standar machines, reduce waste and also important to deployment security. The research was conducted using the observation method and adapted to the literature study. The purpose of this research is to produce an effective and efficient production process in terms of the company’s human and material resources. The result of this study are from the two methods used, namely preventive maintenance and the breakdown method, at the daily check points it is found that the spindle, handle, and worktable / worktable often experience wear and tear, therefore before starting work you must check the engine lubricant in that section, is still there or remains a little. So it can extend the life of the machine.